Cardiac Functional Capacity and QT Prolongation in Patients with CAD in Relation with Exercise-induced BNP Changes - Grybauskienė, R.; Karčiauskaitė, D.; Bertašienė, Z.; Urbonavičienė, G.; Grybauskas, P.; Janėnaitė, J.; Milvidaitė, I.; Blužaitė, I. (Elektronika ir Elektrotechnika, 2006)
The aim of this study was to determine whether responses of plasma BNP during exercise as cardiac functional capacity test are altered in 57 patients with CAD: 36 patients after 2-3 years post MI and 21 patients – 3–4 years after CABG and mitral valve reconstruction surgery, what relation is between BNP exercise changes and QT prolongation, could the dynamics of BNP during exercise test be used in the evaluation of the heart failure. The BNP analysis was performed with Triage (Biosite Diagnostics). The bicycle exercise test has been performed according the protocol and was analyzed by means of ECG system “Kaunas-Krūvis”. QT interval duration was determined from standard 12-lead ECG and corrected by using the Bazett formula. Prolonged QTc was defined as a QTc interval>440ms. Augmented BNP concentration after exercise test was associated with severity of disease, expressed by LV echocardiographic parameters, particularly LV dilatation. Myocardial repolarisation parameters, determined from rest ECG and during the exercise test were significantly associated with BNP concentration at rest and augmentation after exercise test. There was inverse association between cardiac functional capacity and increment of BNP after exercise test. Ill. 7 ,bibl. 20 (in English; summaries in English, Russian and Lithuanian).